The Effectiveness of Social Rights in the EU Social Inclusion and European Governance : A Constitutional and Methodological Perspective - Maccabiani, Nadia (Studi di dritto pubblico - Open Access, 2018)
"Increasing inequalities, social exclusion and poverty within the EU (although at a different scale between States) prove that the effectiveness of social rights falls behind their formal entitlements and their judicial enforceability. Beyond the classical way followed by legal studies in dealing with the issue, the focus would shift to experimental ways better able to cope with the current multifaceted implications of social exclusion, poverty and inequalities for the purpose of effective and improved social inclusion. Indeed, legacies stemming from developments at the European level (recent and less recent) are relevant not only for policy-makers and social scientists but for legal scholars too. These latter are expected to pick up and underline the main aspects of constitutional relevance implied in the process and steer it towards being constitutionally consistent. Against this background, our claim for an interdisciplinary dialogue with social sciences focuses on the constitutional implications underlying the use of social indicators within the European governance framework."